CAMPURAN SAGU DAN ILES-ILES SEBAGAI EKSTENDER PEREKAT UREA FORMALDEHIDA KAYU LAPIS - Suwardi Sumadiwangsa; Yusuf Sudo Hadi; Jhon Novarly Simanjuntak; Suwandi Kliwon (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
In 1984 Indonesia required more than 64.000 ton of wheat flour for extender of urea formaldehyda (UF) adhesive in plywood industry. It is considered more economical when the wheat flour can be substituted by locally available carbohydrate such as sago (Metroxylon sp.). However, sago alone gives poor quality as an extender of UF adhesive.Iles-iles (Amorphophallus oncophyllus) is another potential source of carbohydrate. This contains more protein and mannan than that of wheat flour. Therefore, it is deemed necessary to explore the posisibility of mixing sago and iles-iles as a combined substitute for wheat flour as extender of UF adhesive.This work is intended to obtain optimal ratio of sago and iles-iles formulation, and then to compare its performance with that of wheat flour extender. This study comprise of 5 levels of sago and iles-iles mixed and 3 levels of flour extender, each of which were having 5 replicates aplied for plywood adhesion.The 713 ratio of sago and iles-iles is the same as, if not better than, wheat flour extender. The extender content (X) and plywood bonding strength (Y) for each of the extender was linearly correlated. It is interesting to note that the 614 ratio gives very small slope (B) in its linear regression, in contrast to the others.Although the price of iles-iles was comparable to the wheat flour's, the lles-iles gives higher bonding strength at lower proportion compared with that of the wheat flour extender.